Strategic Planning of Education Information Systems on Bonavita Foundation as a Decision Support in Facing Industrial Revolution 4.0 - Rafika, Ageng Setiani; Ilamsyah, Ilamsyah; Jawahir, Jawahir; Triyono, Triyono (International Journal for Educational and Vocational Studies, 2019)
A very rapid technological development has become a serious concern for the world of education, especially relating to the administration of registration, the learning process and administration of graduation to support industry 4.0. This is due to the inability of human resources in schools to offset the utilization of technology that grows very fast. The problem also impacted the new student administration system, the learning process and graduation as the main activity became late and influential in the lack of enthusiasts to enter as a student. The strategic planning of information systems with Enterprise Architecture Planning (EAP) is a solution to parse and define the main activities run by the Bonavita Education Foundation. Strategic planning can be used as a basis for creating data architectures that are application architecture entities. The technology architecture is designed to illustrate the technology needed to provide a data application environment. The writing of this paper aims to create an educational administration strategy to increase the absorption of prospective students. The interview and observation methods are conducted to obtain accurate data on school leader, administrative staff, alumni and parents of prospective students. Analysis and data processing using value chain. With the planning of information system strategy and information technology it is expected that vocational high schools can face the 4.0 Industrial Revolution and increase the interest of prospective students to enter the school on the Bonavita Foundation without rule out to the vision and mission of the school.